(untitled) (Actual Problems of Mind, 2022)
The article examines the final stage of I. Kant`s "entire critical enterprise" in the context of critical philosophy in general (explained by Kant in his three Critiques: Critique of Pure Reason, Critique of Practical Reason, and Critique of the Power of Judgment). The main idea of the article is that the content of the third Critique is not the aesthetics, teleology, biology, ecology, system theory or philosophy of science, like all of them together, but the reflective power of judgment as one of the higher cognitive faculties of a transcendental subject. It has its own a priori principle (the subjective principle of the formal purposiveness of nature) and its own territory (ein Boden) for rightful use (but not the domain (das Gebiet or ditio)). The author gives three arguments for this idea: (1) it is important to distinguish between critique itself (as propaedeutics) and philosophical doctrine, which consists of the metaphysics of nature and metaphysics of morals; (2) the main task of the third Critique is not the construction of a coherent philosophical system (doctrine), but the solution of a general problem concerning the conditions of the possibility and limits of knowledge of individual formations; (3) before judging numerous particular ideas, it is worth grasping the whole idea, that is, placing the Critique of the Power of Judgment in the context of the "critical enterprise" in general. Kant pays special attention to delineating the limits of rightful use of key terms in a specific context, in particular, such as "the purposiveness of nature" and "the power of judgment". The subject of consideration in the third Critique is the aesthetic judgments of reflection (judgments about the beautiful and the sublime of nature and art), and teleological judgments about objects of nature as ends. If the transcendental principle of the reflective power of judgment in the aspect of its aesthetic variety acts as a constitutive principle for the feeling of pleasure and displeasure, then in the aspect of its teleological variety, it is regulative for the faculty of knowledge. Kant emphasizes that the critique of the power of judgment does not concern to how we know nature, but how we can judge it beyond theoretical cognition in view of the reality of the supersensible, which is the subject of practical philosophy.